Out‐of‐hospital Circulatory Measures to Identify Patients With Serious Injury: A Systematic Review. (20th July 2020) - Newgard, Craig D.; Cheney, Tamara P.; Chou, Roger; Fu, Rongwei; Daya, Mohamud R.; O'Neil, Maya E.; Wasson, Ngoc; Hart, Erica L.; Totten, Annette M.
Abstract: Objective: The objective was to systematically identify and summarize out‐of‐hospital measures of circulatory compromise as diagnostic predictors of serious injury, focusing on measures usable by emergency medical services to inform field triage decisions. Methods: We searched Ovid MEDLINE, CINAHL, and the Cochrane databases from 1996 through August 2017 for published literature on individual circulatory measures in trauma. We reviewed reference lists of included articles for additional relevant citations. Measures of diagnostic accuracy included sensitivity, specificity, and area under the receiver operating characteristic curve (AUROC). Indicators of serious injury included resource need, serious anatomic injury, and mortality. We pooled estimates when data permitted. Results: We identified 114 articles, reporting results of 111 studies. Measures included systolic blood pressure (sBP), heart rate (HR), shock index (SI), lactate, base deficit, and HR variability. Pooled out‐of‐hospital sensitivity estimates were sBP < 90 mm Hg = 19% (95% confidence interval [CI] = 12% to 29%), HR ≥ 110 beats/min = 28% (95% CI = 20% to 37%), SI > 0.9 = 37% (95% CI = 22% to 56%), and lactate > 2.0 mmol/L = 74% (95% CI = 48% to 90%). Pooled specificity estimates were sBP < 90 mm Hg = 95% (95% CI = 91% to 97%), HR ≥ 110 beats/min = 85% (95% CI = 74% to 91%), SI > 0.9 = 85% (95% CI = 72% to 92%), and lactate > 2.0 mmol/L = 62% (95% CI = 51% to 72%). Pooled AUROCs included sBP = 0.67 (95% CI = 0.58 to 0.75), HR = 0.67 (95% CI = 0.56 to 0.79), SI = 0.72 (95% CI = 0.66 to 0.77), and lactate = 0.77 (95% CI = 0.67 to 0.82). Strength of evidence was low to moderate. Conclusions: Out‐of‐hospital circulatory measures are associated with poor to fair discrimination for identifying trauma patients with serious injuries. Many seriously injured patients have normal circulatory measures (low sensitivity), but when present, the measures are highly specific for identifying patients with serious injuries.